PECULIARITIES OF MEXICAN NATIONAL GASTRONOMIC SYMBOLS - Drach , Karina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
This article studies national gastronomic symbols of Mexicans and their special value in cultural and language world pictures in order to conduct etymologic, linguo-cultural and conceptual analysis of meanings of lexical and phraseological units. The object of the research is Mexican national gastronomic symbols as the target of reflection of gastronomic picture of the world of Mexicans. The article grounds on the role of national gastronomic symbols and the variability of their reflections in the language, emphasizes that the language of symbols is the universal language of culture, which expresses its specific features. The author uses the descriptive method of research with the elements of comparable and dialectical analysis for the complex study of the Mexican national gastronomic symbols and for determination their semantic and culturological peculiarities. The material for the analysis is selected by means of continuous selection method. The author pays special attention to semantics of gastronomic symbols, their cultural connotations and means of verbalization. The results of the research can be used in language geography courses, in the research of the problems connected with national and cultural features of the Mexican variant of the Spanish language, as well as in the study of cross-cultural communication. National gastronomic symbols are characterized by the biggest quantity of associations in language consciousness of Mexicans and wide range of senses. ______________ References • Alefirenko,N. F. «Sinergetika kulturnogo koncepta i znaka v sisteme yazyka i tekste.» Kulturnye aspekty v yazyke i tekste (Belgorod, 2005): 8–21. • Bart,R. Sistema mody. Stati o semiotike kultury (Moskva, Izd-vo imeni Sabashnikovyh, 2003), 511. • Berezovich,E. L. Yazyk i tradicionnaya kultura (Moskva, Indrik, 2007), 600. • Gudkov,D. B. «Edinicy kodov kultury: problemy semantiki.» Yazyk, soznanie, kommunikaciya 26 (2004): 39–50. • Kovshova,M. L. «Semantika i pragmatika frazeologizmov (lingvokulturologicheskij aspekt).» (Dis. d-ra filol. nauk, Moskva, 2009), 654. • Krasnyh,V. V. Etnopsiholingvistika i lingvokulturologiya: Kurs lekcij (Moskva, ITDGK «Gnozis», 2002), 284. • Losev,A. F. Problema simvola i realisticheskoe iskusstvo, 2-e izd., ispr. (Moskva, Iskusstvo, 1995), 320. • Lotman,Yu. M. «Vnutri myslyashih mirov.» Semiosfera (Sankt-Peterburg, 2001): 150–390. • Pimenova,M. V. «Kody kultury i problemy klassifikacii konceptov.» Yazyk. Tekst. Diskurs 5 (2007): 79–85. • Teliya,V. N. «O fenomene vosproizvodimosti yazykovyh vyrazhenij.» Yazyk. Soznanie. Kommunikaciya 30 (2005): 4–42. • Ter-Minasova,S. G. Yazyk i mezhkulturnaya kommunikaciya (Moskva, Slovo / Slovo, 2008), 264. • Chesnokova,O. S. «Ispanskij yazyk v Meksike: yazykovaya kartina mira.» Monografiya (Moskva, Izd-vo RUDN, 2006), 238. • Yurina,E. A. «Obraznyj stroj yazyka kak lingvokognitivnyj fenomen i leksiko-frazeologicheskie sredstva ego eksplikacii.» Frazeologiya i poznanie (Belgorod, 2010): 289–294. • Akademichnij tlumachnij slovnik ukrayinskoyi movi, dostup http://sum.in.ua/ • Ispano-russkij slovar. Latinskaya Amerika: 50000 slov i slovosochetanij, pod red. N. M. Firsovoj (Moskva, Nauka, 1998), 606. • Ispansko-russkij frazeologicheskij slovar, pod red. E. I. Levintovoj (Moskva, Russkij yazyk, 1985), 1080. • Cabrera Luis. Diccionario de aztequismos (México, Colofón, S.A., 2002), 170. • Diccionario de la lengua española, access https://dle.rae.es/ • Mejía Prieto. Así habla el mexicano: Diccionario básico de mexicanismos (México, Panorama Editorial, S.A. 1984), 144. • Morínigo, M.A. Diccionario de americanismos (Buenos Aires, Muchnik, 1966), 738.